A Class II KNOX Gene, KNAT7-1, Regulates Physical Seed Dormancy in Mungbean [Vigna radiata (L.) Wilczek] - Laosatit, Kularb; Amkul, Kitiya; Yimram, Tarika; Chen, Jingbin; Lin, Yun; Yuan, Xingxing; Wang, Lixia; Chen, Xin; Somta, Prakit (Frontiers in Plant Science, 2022)
Seed dormancy in wild mungbean (Vigna radiata var. sublobata) may be useful for breeding of cultivated mungbean (var. radiata) with pre-harvest sprouting resistance. Previous studies have identified two major QTLs for seed dormancy, HsA and Sdwa5.1.1+, in wild mungbean that are possibly the same locus or linked. However, these QTL have not been confirmed/verified and the molecular basis of the seed dormancy in mungbean is not yet known. In this study, we aimed to finely map the Sdwa5.1.1+ and identify candidate gene(s) for this locus. Microscopic observations revealed that wild mungbean “ACC41” seeds had the palisade cuticle layer, while cultivated mungbean “Kamphaeng Saen 2” (KPS2) seeds lacked this layer. Fine mapping using an F2 population developed from a cross between ACC41 and KPS2 revealed two linked QTLs, Sdwa5.1.1+ and Sdwa5.1.2+, controlling seed dormancy. The Sdwa5.1.1+ was confirmed in an F2:3 population derived from the same cross and mapped to a 3.298-Kb region containing only one gene LOC106767068, designated VrKNAT7-1, which encodes transcription factor KNOTTED ARABIDOPSIS THALIANA7 (KNAT7), a class II KNOTTED1-LIKE HOMEOBOX (KNOX II) protein. VrKNAX7 sequence alignment between ACC41 and KPS2 revealed several polymorphisms in the coding, untranslated and promoter regions. Quantitative real-time PCR analysis revealed that expression of VrKNAT7-1 and VrCYP86A, a putative downstream regulation of VrKNAT7-1, in seed coat of ACC41 is statistically much higher than that of KPS2. Altogether, these results indicate that VrKNAT7-1 controls physical seed dormancy in the wild mungbean ACC41.